2012
DOI: 10.1038/bjc.2012.167
|View full text |Cite
|
Sign up to set email alerts
|

Aurora kinase A outperforms Ki67 as a prognostic marker in ER-positive breast cancer

Abstract: Background:Proliferation has emerged as a major prognostic factor in luminal breast cancer. The immunohistochemical (IHC) proliferation marker Ki67 has been most extensively investigated but has not gained widespread clinical acceptance.Methods:We have conducted a head-to-head comparison of a panel of proliferation markers, including Ki67. Our aim was to establish the marker of the greatest prognostic utility. Tumour samples from 3093 women with breast cancer were constructed as tissue microarrays. We used IHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 52 publications
9
60
1
Order By: Relevance
“…These data are in compliance with recently published data showing that elevated Aurora kinase A expression was significantly associated with recurrence in ER-positive tumors. [48][49][50] Our finding that high Aurora kinase A expression is an independent predictor of recurrence in tamoxifen-treated breast cancer patients merits further investigation of Aurora kinase A as a new potential biomarker for tamoxifen resistance. and MCF-7/182 R -6 (182 R -6) by long-term treatment with 100 nM fulvestrant (ICI182 780; Tocris Bioscience, Bristol, UK) as previously described.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…These data are in compliance with recently published data showing that elevated Aurora kinase A expression was significantly associated with recurrence in ER-positive tumors. [48][49][50] Our finding that high Aurora kinase A expression is an independent predictor of recurrence in tamoxifen-treated breast cancer patients merits further investigation of Aurora kinase A as a new potential biomarker for tamoxifen resistance. and MCF-7/182 R -6 (182 R -6) by long-term treatment with 100 nM fulvestrant (ICI182 780; Tocris Bioscience, Bristol, UK) as previously described.…”
Section: Discussionmentioning
confidence: 90%
“…Clinical data have shown that the prognostic significance of Aurora kinase A was limited to ER+ breast cancer, suggesting a link between Aurora kinase A and ER. 48 In support of this, Aurora kinase A has been shown to phosphorylate ER at Ser167/Ser305, leading to increased ER transactivation and decreased tamoxifen sensitivity. 49 We observed that the ER pioneer factor FOXA1, which is required for ER signaling in tamoxifen-resistant cells, 13 was decreased on treatment with the Aurora kinase inhibitor JNJ-7706621 in tamoxifen-resistant cells, indicating that ER signaling was impaired in these cells.…”
Section: Discussionmentioning
confidence: 96%
“…An effort towards harmonization between researchers is being driven by the International Ki67 in Breast Cancer Working Group which has initiated a pilot between-laboratory quality assessment scheme. Recommendations on pre-analytical and analytical procedures, interpretation, scoring and data handling have been given in order to be followed by all new researchers interested to the field to standardize their procedures [74]. …”
Section: Is Ki67 Ready For Clinical Use?mentioning
confidence: 99%
“…An estimate for the prognostic effect of KI67 status was based on an analysis of data from the SEARCH (studies of epidemiology and risk factors in cancer heredity) study [6]. SEARCH is a large prospective population-based study of women diagnosed with breast cancer, including prevalent cases diagnosed before the age of 55 years during 1991-1996 and still alive in 1996, and incident cases consisting of women under the age of 70 years diagnosed after 1996.…”
Section: Prognostic Effect Of Tumour Ki67 Statusmentioning
confidence: 99%
“…The classifications based on gene expression can be recapitulated using immunohistochemistry (IHC) [4,5]. While AURKA expression has been shown to be a more powerful prognosticator than KI67 [6], KI67 has been advocated as the marker of choice for measuring and monitoring tumour proliferation [7]. Furthermore, KI67 expression has been used with other IHC markers to identify the proliferative subgroup of HER2-& ER+ cases with a poor outcome [8], who may benefit from adjuvant chemotherapy.…”
Section: Introductionmentioning
confidence: 99%